2014
DOI: 10.1371/journal.pone.0089554
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for the Implementation of Primary Prevention and Health Promotion Activities in Primary Care: A Synthesis through Meta-Ethnography

Abstract: BackgroundEvidence supports the implementation of primary prevention and health promotion (PP&HP) activities but primary care (PC) professionals show resistance to implementing these activities. The aim was to synthesize the available qualitative research on barriers and facilitators identified by PC physicians and nurses in the implementation of PP&HP in adults.Methods and FindingsA systematic search of three databases was conducted and supported by manual searches. The 35 articles included were translated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
0
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(256 citation statements)
references
References 48 publications
(150 reference statements)
11
223
0
22
Order By: Relevance
“…As compared with other types of clinicians, primary care staff may have various advantages, such as greater accessibility, closeness, knowledge of patients, and less stigma, as well as continuity of care and a comprehensive and holistic focus, 52 though there may be certain drawbacks, such as the need for training and lack of time to carry out the intervention. 53 A recent overview of reviews 23 reported that most trials to prevent depression have been conducted by mental health specialists, to a lesser extent by educational staff (for children and adolescents), more sparsely by lay persons, and rarely by primary care professionals. Further trials with primary care staff as providers of depression interventions are needed.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with other types of clinicians, primary care staff may have various advantages, such as greater accessibility, closeness, knowledge of patients, and less stigma, as well as continuity of care and a comprehensive and holistic focus, 52 though there may be certain drawbacks, such as the need for training and lack of time to carry out the intervention. 53 A recent overview of reviews 23 reported that most trials to prevent depression have been conducted by mental health specialists, to a lesser extent by educational staff (for children and adolescents), more sparsely by lay persons, and rarely by primary care professionals. Further trials with primary care staff as providers of depression interventions are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is the need of a real community-based collaboration, meaning that the primary care professionals are playing an active role, sharing common goals with other stakeholders and working together (Carmola Hauf and Bond, 2002;Woltmann et al, 2012). Perceived lack of skills, inexistent collaboration between professionals, and scarce (or absent) evidence are important barriers to the implementation of overall health promotion activities (Rubio-Valera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Porém, nem sempre essa é uma verdade, constatada nos diversos serviços de saúde, inclusive no ensino. A esse respeito, estudos mostram que a formação profissional na área da saúde ainda sofre influência do modelo biomédico, que desconsidera o fato da pessoa cuidada viver dentro de um contexto, ter um nome, família, vida social, não querer ser identificado por meio de um número ou por uma doença 11,12 .…”
Section: Resultsunclassified